Transcription profiles of mitochondrial genes correlate with mitochondrial DNA haplotypes in a natural population of Silene vulgaris - Elansary, Hosam O; Müller, Karel; Olson, Matthew S; Štorchová, Helena (Bmc plant biology, 2010)
BACKGROUND: Although rapid changes in copy number and gene order are common within plant mitochondrial genomes, associated patterns of gene transcription are underinvestigated. Previous studies have shown that the gynodioecious plant species Silene vulgaris exhibits high mitochondrial diversity and occasional paternal inheritance of mitochondrial markers. Here we address whether variation in DNA molecular markers is correlated with variation in transcription of mitochondrial genes in S. vulgaris collected from natural populations. RESULTS: We analyzed RFLP variation in two mitochondrial genes, cox1 and atp1, in offspring of ten plants from a natural population of S. vulgaris in Central Europe. We also investigated transcription profiles of the atp1 and cox1 genes. Most DNA haplotypes and transcription profiles were maternally inherited; for these, transcription profiles were associated with specific mitochondrial DNA haplotypes. One individual exhibited a pattern consistent with paternal inheritance of mitochondrial DNA; this individual exhibited a transcription profile suggestive of paternal but inconsistent with maternal inheritance. We found no associations between gender and transcript profiles. CONCLUSIONS: Specific transcription profiles of mitochondrial genes were associated with specific mitochondrial DNA haplotypes in a natural population of a gynodioecious species S. vulgaris.Our findings suggest the potential for a causal association between rearrangements in the plant mt genome and transcription product variation.
Keywords: DNA, Plant; DNA, Mitochondrial; Silene; polymorfismus délky restrikčních fragmentů; Genes, Mitochondrial; stanovení celkové genové exprese; Polymorphism, Restriction Fragment Length; Genetics, Population; typy dědičnosti; Inheritance Patterns; Haplotypes; mitochondriální geny; mitochondriální DNA; DNA rostlinná; Sequence Analysis, DNA; haplotypy; sekvenční analýza DNA; Gene Expression Profiling; populační genetika